Flexural and Shear Strength of RC Beam with Embedded Polystyrenes - Jen Hua Ling; Danson Tzet Lung Tan; Yong Tat Lim (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2026)
This study examines the structural performance and material efficiency of reinforced concrete (RC) beams embedded with trapezoidal polystyrene, tested under flexural and shear loadings. The integration of polystyrene aims to reduce concrete volume while maintaining structural integrity. Twelve specimens were tested under four-point static loading, including five different polystyrene configurations and one control specimen for each loading type. Performance was evaluated based on load-displacement behavior, structural capacity, and material efficiency (i.e., strength gain vs concrete volume reduction). Results indicate that beams incorporating polystyrene remain functional. However, not all configurations increased load-bearing capacity; for example, PB5 showed decreased capacity. Performance is significantly influenced by the geometry of the embedded polystyrene, with increasing width having a more detrimental effect than depth. Among the specimens, PB2 exhibited the best overall performance, achieving 10% higher flexural capacity and 18% greater shear capacity despite a 10% reduction in concrete volume, resulting in 22% and 31% higher material efficiency under flexural and shear loadings, respectively. Some specimens, such as PB5, showed decreased capacity. These gains, however, were offset by lower cracking resistance and reduced ductility, which could limit the beam’s serviceability and affect its suitability for structural applications requiring high deformation capacity or crack control. Despite its potential, the use of polystyrene in RC beams presents practical challenges, including the study’s limited replication, construction complexity, and fire safety concerns, which must be addressed before broader implementation in structural applications.